A comparative surface topographical analysis of explanted total knee replacement prostheses: Oxidised zirconium vs cobalt chromium femoral components. (December 2017) - Kennard, Emma; Scholes, Susan C.; Sidaginamale, Raghavendra; Gangadharan, Rajkumar; Weir, David J.; Holland, James; Deehan, David; Joyce, Thomas J.
Highlights: Non-contacting profilometry is used to compare the surface roughness of retrieved OxZr & CoCr TKRs. Both OxZr and CoCr femoral components show increased surface roughness parameters following time in vivo . No difference was seen between the surface roughness parameters of retrieved OxZr and CoCr femoral components. Further analysis of explanted prostheses is recommended to continue to investigate the benefits and limitations of OxZr as a femoral component material. Abstract: It has been proposed that an increased surface roughness of the femoral components of Total Knee Replacements (TKRs) may be a contributing factor to the accelerated wear of the polyethylene (PE) bearing and ultimately prosthesis failure. Oxidised Zirconium was introduced to the orthopaedic market in an attempt to reduce PE wear associated failures and increase the longevity of the prosthesis. In this study, non-contacting profilometry was used to measure the surface roughness of the femoral components of 6 retrieved TKRs (3 Oxidised Zirconium (OxZr) and 3 Cobalt Chromium alloy (CoCr) femoral components) and 2 as-manufactured femoral components (1 OxZr and 1 CoCr). A semi-quantitative method was used to analyse the damage on the retrieved PE components. The S a values for the retrieved OxZr femoral components ( Sa = 0.093 µm ± 0.014) and for the retrieved CoCr femoral components ( Sa = 0.065 µm ± 0.005) were significantly greater ( p < .05) than the roughness values for the as-manufactured femoral components (OxZr Sa = 0.061 µm ± 0.004 and CoCr Sa = 0.042 µm ± 0.003). No significant difference was seen between the surface roughness parameters of the retrieved OxZr and retrieved CoCr femoral components. There was no difference between the PE component damage scores for the retrieved OxZr TKRs compared to the retrieved CoCr TKRs. These results agree with other studies that both OxZr and CoCr femoral components roughen during time in vivo but the lack of difference between the surface roughness measurements of the two materials is in contrast to previous topographical reports. Further analysis of retrieved OxZr TKRs is recommended so that a fuller appreciation of their benefits and limitations be obtained.